The Interaction Among Capital Structure, Dividend Policy and Ownership Structure: Evidence from the Iberian Markets (International Journal of Business Innovation, 2023)
The objective of this study is to explore the interrelationship among ownership structure, capital structure and dividend policy, because prior empirical studies analysed the capital structure or the dividend policy in isolation, but these two corporate finance decisions can be interrelated, affecting each other. Finding this gap, this paper analyses the interrelationship among ownership structure, capital structure and dividend policy, using approaches to remove simultaneous bias. In order to analyse the association among these companies’ decisions, we consider a sample of Portuguese and Spanish listed firms, for the period between 1992 and 2016, employing panel data regression, as well as the two stage least squares (2SLS) and the three stage least squares (3SLS) in order to address for endogeneity issues. Different estimation methods are implemented and compared by means of a robust residual analysis. The results indicate that the firm´s payout is affected by the firm size. Also, we find evidence that managerial ownership and firms’ profitability have an impact on leverage, which is in accordance with the pecking order theory.
Keywords: ownership structure; capital structure; dividend policy